A famennian (late Devonian) conodont assemblage from brachiopod–rich limes-tones of the Djravank section (Southern Armenia) - A. Grigoryan; V. Serobyan; C. Randon; R. Mayilyan; N. Avagyan; T. Danelian (ՀՀ ԳԱԱ հրատ.)
Numerous conodont elements were yielded from a sandy brachiopod–rich limestone after processing with formic acid. The sample comes from a ca. 25 m–thick sequence of well–bedded nodular limestones, cropping out along a newly explored section (Djravank), situated on the south bank of the river Arpa, of the river Arpa, near the village of Arpi in Vayots Dzor region. Կոնոդոնտային բազմաթիվ էլեմենտներ են կորզվել բրախիոպոդներով հարուստ ավազային կրաքարից, թթվով հինգ նմուշ մշակելուց հետո: Նմուշը վերցվել է լավ շերտավորվածությամբ արտահայտված նոդուլային կրաքարերից կազմված մոտ 25մ հզորությամբ նստվածքային հաջորդականությունից, որոնք մերկանում են վերջերս ուսումնասիրվածված Ջրավանքի կտրծվածքի երկայնքով: Կտրվածքը տեղակայված է Արփի գյուղից հարավ, Արփա գետի աչափնյա մասում: Многочисленные элементы конодонтов были извлечены из песчаного известняка, богатого брахиоподами. Образец был взят из приблизительно 2 метровой толщи с хорошо выраженной слоистостью желвакообразных известняков, обнажающиеся вдоль недавно изученного разреза (Джраванк), расположенного южнее села Арпи на правом берегу реки Арпа.
Keywords: Science; Geology; Stratigraphy